2017
DOI: 10.1111/jph.12596
|View full text |Cite
|
Sign up to set email alerts
|

Vessel occlusion in three cultivars of Olea europaea naturally exposed to Xylella fastidiosa in open field

Abstract: Xylella fastidiosa is a Gram‐negative, xylem‐limited, bacterium which is responsible, in Italy, for the olive quick decline syndrome (OQDS). The disease is caused by the subspecies pauca and emerged a few years ago in the Apulia province of Lecce, in the Salento peninsula, on Olea europaea plants. X. fastidiosa can infect different plant species and is well known in California as the causal agent of Pierce's disease on grape. Infections of susceptible hosts with X. fastidiosa are known to result in xylem vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
(49 reference statements)
5
27
0
Order By: Relevance
“…Our samples showed an erratic distribution of X. fastidiosa, especially in the branches, confirming previous reports [25,26,41]. The taxonomic composition of the microbiota showed hundreds of families and genera, which is in agreement with the data available from other tree species [43,44].…”
Section: Discussionsupporting
confidence: 92%
“…Our samples showed an erratic distribution of X. fastidiosa, especially in the branches, confirming previous reports [25,26,41]. The taxonomic composition of the microbiota showed hundreds of families and genera, which is in agreement with the data available from other tree species [43,44].…”
Section: Discussionsupporting
confidence: 92%
“…In the majority of the Xylella -colonized vessels, only a few bacterial cells or small aggregates are seen, suggesting that vessel blockage is not a colonization strategy of Xylella , but rather a consequence of endophytic colonization ( Newman et al, 2003 ). The same colonization behavior has been observed for CoDiRO strain in olive trees ( De Benedictis et al, 2017 ). Our findings in branches are similar to what was reported for olive trees, i.e., rare and solitary bacterial cells in the xylem vessels ( De Benedictis et al, 2017 ).…”
Section: Discussionsupporting
confidence: 83%
“…The same colonization behavior has been observed for CoDiRO strain in olive trees ( De Benedictis et al, 2017 ). Our findings in branches are similar to what was reported for olive trees, i.e., rare and solitary bacterial cells in the xylem vessels ( De Benedictis et al, 2017 ). Differently from De Benedictis et al (2017) , however, we found vessels blocked by large X. fastidiosa aggregates clearly visible in xylem petioles of symptomatic plants.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…From there, the bacterium spread to the northwest provinces of Brindisi and Taranto, and some infected trees have also been recently reported in the province of Bari (northeast). A large number of publications about the impact of Xf in Puglia are available; a small selection is included in the references [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%